Answer:
Gradient = Change in y / Change in x
Gradient = (-7-3) / (0-4)
Gradient = -10/-4
Gradient = 2.5
So the answer is 10/4, which is 2.5
Answer:
*In Explanation
Step-by-step explanation:
<u>1) Start by just substituting the value of x (given in equation 1) into the second equation:</u>
y = 3x - 1
y = 3(2) - 1
y = 6-1 = 5
<u>2) Since both equations have x on one side, make both equations equal to one another:</u>
2y + 4 = 9 - 3y
<u>Solve for y:</u>
5y = 5
y = 1
<u>Plug y = 1 into either one of the given equations and solve for x:</u>
I'll use first equation:
x = 2y + 4
x = 2(1) + 4
x = 6
<u>3) When substituting X into the second equation, remember to use parenthesis:</u>
The student was substituting x from equation 1 into equation 2, but they forgot to multiply ALL of 2y + 3 by 2.
x = 2y + 3
Substitute into 2nd eqn:
y = 2(2y + 3) - 9
Answer:
Y = -10X - 5
Step-by-step explanation:
Y = mX + b
m - slope
b - y - intercept.
Answer:
Answer is in the explanation
Step-by-step explanation:
I don't know exactly word from word what your choices look like...
but I can describe per each box what happened in my own words:
First box: They multiply first equation by 3 and the second equation by 2 to obtain the equations in that first box.
Second box: They subtracted the two equations in the first box to obtain 1x+0y=2 which means 1x=2 or x=2 (this is called solving a system by elimination
Third box: They used their first original equation (before the multiplication manipulation) and plug in the value they got for x which was 2 giving them 3(2)-2y=10
Fourth box: They simplified the equation 3(2)-2y=10 by performing the multiplication 3(2) giving them 6-2y=10
Fifth box: They subtracted 6 on both sides giving them -2y=4
Sixth box: They divided both sides by -2 giving them y=-2
I will summarize then what I wrote above:
1st box: Multiplication Property of Equality
2nd box: Elimination
3rd box: Substitution (plug in)
4th box: Simplifying
5th box: Subtraction Property of Equality
6th box: Division Property of Equality
The image of U will be (2,-1)